Teaching Human-Computer Interaction Modules—And Then Came COVID-19 - De Wet, Lizette (Frontiers in Computer Science, 2021)
In teaching Human-Computer Interaction at university level, it has always been beneficial to explain the related theory and engage students in a practical way, whether individually or in groups. And then came COVID-19. Face-to-face classes were replaced by emergency remote teaching methods. Students became student numbers in cyber space. The danger became real to convert back to the traditional way of presenting lectures, namely a lecturer doing all the talking and the students being the passive audience. This paper describes how the author had to adapt and innovate in terms of teaching Human-Computer Interaction modules to university students in a practical way during the COVID-19 pandemic. Frequent online quizzes, audio messages, online group discussion, smaller topic-dedicated practical activities, and webinars encouraging student participation, were employed. Instead of having access to eye-tracking technology in a usability laboratory, students had to innovate for usability evaluation assignments by employing observation, think-aloud protocols, and performance and self-reported metrics as data gathering methods. The laboratory had to be replaced by COVID-compliant places of residence. The outcomes of adapting previously-used teaching methods and inventing new ways to encourage student participation, were surprisingly positive. An additional advantage was that many of these methods turned out to be so successful that their application could be continued and extended to post-pandemic times for a blended learning approach to further enrich Human-Computer Interaction teaching.